Current and future circulating biomarkers for cardiac amyloidosis - LUCIANI Marco; TRONCONE Luca; MONTE Federica DEL (Acta Pharmacologica Sinica, 2018)
Cardiac amyloidosis (CA) comprises a heterogeneous group of medical conditions affecting the myocardium. It presents with proteinaceous infiltration with variable degrees of severity, prevalence and evolution. Despite this heterogeneity, erroneous protein folding is the common pathophysiologic process, yielding the formation of a single misfolded protein (monomer) that progressively evolves and ultimately forms amyloid fibers. Additionally, by seeding out from the organs of origin, intermediates called oligomers metastasize and restart the process. Such self-echoing behavior makes the secondary affected organs as important as the primary ones. Unfortunately, CA can be clinically challenging and only suggestive in a late stage of its natural history, leaving a narrow therapeutic time window available. In light of the evolutionary nature of amyloidosis, here, we propose a new classification of the currently used biomarkers based on time stages with different specificity and applicability across CA subtypes. Early markers (free light chains, serum amyloid A, β2-microglobulin, osteopontin and osteoprotegerin) can be employed for disease detection. Intermediate markers [soluble suppression of tumorigenicity 2 (sST-2), midregional proadrenomedullin (MR-proADM), von Willebrand factor (vWF), hepatocyte growth factor (HGF), matrix metalloproteinases (MMPs) and tissue inhibitor metalloproteinases (TIMPs)] can provide information on the biological mechanisms of myocardial damage. As in heart failure, late-stage biomarkers (troponins and natriuretic peptides) can help clinicians with prognosis and therapeutic response evaluation in CA. Such findings have generated a remarkable foundation for our current knowledge on CA. Nevertheless, we envision a future class of biomarkers targeted at upstream events capable of detecting folding defects, which will ultimately expand the therapeutic window.